Infiltração da água em latossolo vermelho distroférrico utilizando infiltrômetros de cilíndro único - Frigo, Jianice Pires (2017)
The infiltration process understanding and its relationship with soil properties is essential for the efficient management of soil and water. Thus, this paper aimed at evaluating water infiltration in an area of Oxisol, using single ring infiltrometers with different diameters. In addition, it also aimed at comparing the performance of 7 cm (A7) and 15 cm (A15) cylinders, matching soil moisture and bulk density to water infiltration and evaluating spatial distribution of infiltration. For this purpose, 24 data points were evaluated, placed in 8 plots of a circular area prepared for permaculture cropping, named as Mandala. Shewhart graphs and process capability index were used to compare cylinders and the inverse of distance square for data interpolation. It was observed that the average stable infiltration rate, determined with A7 cylinder, was 196.79 mm h-1 and with A15 cylinder was 187.30 mm h-1, consequently, there was a difference of 5.6%. The process capacity was estimated at 0.61 for A7 and 1.62 for A15, considered adequate for A15 and inadequate for A7 cylinder. Thus, it was concluded that the infiltration rates that were stabilized and determined by the cylinders were compatible with the rates determined by other methods in other papers. Regarding the performance of single-ring infiltrometers, it is concluded that, although both cylinders presented controlled processes, and did not differ statistically, cylinder A15 presented less variability on data, and may be considered adequate due to its process capability index.